Mechanical Response and Control Measures of Pile Foundations under Close-Range Shield Tunneling in Water-Rich Sandy Pebble Strata - Yanpeng Du; Peng Zhang; Jiabing Zhang (Advances in Civil Engineering)
By relying on the foundation engineering of pile foundations for the Chengdu Metro Line 27 shield tunneling through interchange bridges, three-dimensional numerical simulation results are used to verify field measurements. This study investigates the horizontal displacement, vertical displacement, and stress characteristics of the pile foundation during shield tunneling considering the coupling effect of seepage stress. Additionally, protective measures and reinforcement effects for pile foundations near the tunnel are discussed. Results show that the deformation caused by shield tunneling in gravel strata mainly affects piles within 10 ring widths before and after the piles. During right-side excavation, the bending moment of the pile body exhibits an inverted “S” distribution, while during left-side excavation, it is symmetrically distributed, with the maximum bending moment and axial force occurring at the same buried depth as the tunnel crown. Vertical displacement of the pile body is divided by the horizontal position at the top of the tunnel, with upper pile settlement and lower pile uplift, reaching maximum at the pile top. Horizontal displacement of the pile body shows an “arch” distribution, with stress concentration near the tunnel, indicating an overall trend of the pile foundation moving away from the tunnel. Based on the mechanical response of the pile foundation, control measures such as ground pregrouting with sleeve valve pipes and semicircular grouting inside the tunnel are proposed. Optimized reinforcement parameters are obtained through three-dimensional numerical simulation, resulting in an 80% reduction in horizontal displacement, an 80.5% reduction in vertical displacement, a 70% reduction in pile axial force, and a 67% reduction in pile bending moment under the optimal reinforcement conditions. The research provides important theoretical basis for revealing the impact laws of shield tunneling through pile foundations in gravel strata and for controlling bridge pile deformation.